Real-time control of bilateral teleoperation system with adaptive computed torque method - Abut, Tayfun; Soyguder, Servet (Emerald Group Publishing Ltd, 2017)
Purpose - This paper aims to use the adaptive computed torque control (ACTC) method to eliminate the kinematic and dynamic uncertainties of master and slave robots and for the control of the system in the presence of forces originating from human and environment interaction. Design/methodology/approach - In case of uncertainties in the robot parameters that are utilized in teleoperation studies and when the environment where interactions take place is not known and when there is a time delay, very serious problems take place in system performance. An adaptation rule was created to update uncertain parameters. In addition to this, disturbance observer was designed for slave robot. Lyapunov function was used to analyze the system's position tracking and stability. A visual interface was designed to ensure that the movements of the master robot provided a visual feedback to the user. Findings - In this study, a visual interface was created, and position and velocity control was achieved utilizing teleoperation; the system's position tracking and stability were analyzed using the Lyapunov method; a simulation was applied in a real-time environment, and the performance results were analyzed. Originality/value - This study consisted of both simulation and real-time studies. The teleoperation system, which was created in a laboratory environment, consisted of six-degree-of-freedom (DOF) master robots, six-DOF industrial robots and six-DOF virtual robots.
Keywords: Teleoperation; Adaptive computed torque control; Disturbance observer; Industrial robot; Lyapunov function